PEDAGOGICAL AND PSYCHOLOGICAL APPROACHES TO THE DEVELOPMENT OF SELF-ESTEEM IN PRESCHOOL CHILDREN - Atabaeva Dilshoda Azatovna (International Journal of Literature and Language Studies, 2026)
This article provides a theoretical analysis of pedagogical and psychological approaches to the development of self-esteem in children attending preschool educational institutions. The psychological essence of the concept of self-esteem, its role in the personal development of preschool children, and its relationship with social adaptation and future educational success are examined. The article highlights the influence of play activity, social communication, creative activity, and a supportive pedagogical and psychological environment created by the teacher on the formation of children’s self-esteem. The study is theoretical in nature and is developed in accordance with the requirements of international academic journals, offering practical relevance for researchers in the field of preschool education.